IL-33/ST2 axis promotes the inflammatory response of nasal mucosal epithelial cells through inducing the ERK1/2 pathway. Issue 6 (August 2020) - Li, Yun-Qiu; Zhong, Yu; Xiao, Xu-Ping; Li, Dan-Dan; Zhou, Zheng; Tian, Yan-Yan
Allergic rhinitis (AR) is a nasal mucosal inflammatory disease mediated by environmental allergens. At present, the relationship between the IL-33/ST2 axis, ERK1/2 pathway and AR progression needs further exploration. In our study, an AR model was constructed in vitro by treating HNEpC cells with Der p1. qRT-PCR was applied to assess the mRNA levels of IL-33, ST2, TNF-α, IL-6, and IL-8. Western blotting was used to measure the protein levels of IL-33, ST2, and the downstream proteins p-ERK1/2, ERK1/2, p-RSK, and RSK. IL-6, IL-8, IL-33, and TNF-α protein levels in cell supernatants were evaluated by ELISA. Flow cytometry was performed to check cell apoptosis of HNEpC in the presence or absence of Der p1. Our results indicate that the relative levels of IL-33, ST2, TNF-α, IL-6, and IL-8 were increased significantly in the AR model group. The above effects were notably reversed after transfection with shIL-33 or shST2. IL-33 stimulation further resulted in the increase in both ST2 and inflammation-associated cytokines, and these effects were restored after shST2 treatment. Also, the levels of inflammatory factors induced by IL-33 stimulation or ST2 overexpression were reversed after applying an ERK1/2 pathway blocker. In conclusion, IL-33/ST2 mediated inflammation of nasal mucosal epithelial cells by inducing the ERK1/2 pathway.